François Hartog: history in a catastrophic time - Aravena Núñez, Pablo (Cuadernos de Historia, 2015)
Interview given by french historian François Hartog, during his stay in Valparaíso at the end of 2013. Subjects on his ouvre will be covered, also his thesis where he holds that we live in a period marked by “regimes of presentist historicity”, the meaning of heritage’s overproduction, the memory boom and the link between the future’s block and a dominant ideology.